Peran E-Lifestyle, Budaya Digital, Dan E-Payment Terhadap Perilaku Konsumtif Generasi Y Dalam Bertransaksi di E- Commerce - Novia Indah Lestari; Mery Ramadani; Sutikno Sutikno (EKONOMI KEUANGAN DAN BISNIS, 2022)
Technology has changed people's lifestyles and culture, including their shopping behavior which is more directed towards consumptive behavior. The ease of making digital payment transactions (e-payments) also affects wasteful behavior among Generation Y. In addition, the impact of the Covid-19 pandemic which requires consumers to limit distance has made them more aggressive in making purchases through e-commerce applications. This research was conducted on Generation Y consumers who have made purchases on e-commerce and paid e- payment at least 3 times a month. The sample is taken from 100 respondents with a purposive sampling technique. The research data that has been collected will be processed using the structural equation model (SEM) – PLS. The results of this study indicate that the variables of e-lifestyle, digital culture, and e-payment have a positive effect on increasing the consumptive behavior of Generation Y in shopping at e-commerce.